ответ:
\frac{13k-4}{3-13k}+ \frac{x}{3-13k}=1
\frac{13k-4+x}{3-13k}= \frac{3-13k}{3-13k}
\frac{13k-4+x}{3-13k}- \frac{3-13k}{3-13k} =0
\frac{13k-4+x-(3-13k)}{3-13k}=0
\frac{13k-4+x-3+13k}{3-13k}=0
\frac{26k-7+x}{3-13k}=0
\left \{ {{26k-7+x=0} \atop {3-13k \neq 0}} \right. ; \left \{ {{x=-26k+7} \atop {k \neq \frac{3}{13} }} \right. ; \left \{ {{x=7-26k} \atop {k \neq \frac{3}{13} }} \right.
ответ: если k \neq \frac{3}{13} , то x=7-26k
объяснение:
8x^6 y^6*(3y)^2 / yx^2 * (5y^2 x)^2
8x^4 y^5*9y^2 / 25y^4 x^2
8x^2 y^5*9 / 25y^2
8x^2 y^3*9 / 25
72x^2 y^3 / 25
все